An approach to the evaluation of iron status and the prevention of iron deficiency - Macphail, Andrew, Patrick (My University, 1981)
This thesis took advantage of the very wide spectrum of iron status encountered amongst the people of Southern Africa. Established methods of measuring iron status were used to illustrate features of dietary iron overload, iron deficiency and the relationship between maternal and infant iron status. Attention was also paid to the prevention of iron deficiency in the heterogeneous South African population. In a comparative autopsy study measurement of hepatic iron showed a significant reduction in the prevalence and severity of dietary iron overload in urban black males over the past 17 years. Although hepatic iron concentration rose with age, there had been no iron accum ulation during this period. Liberalisation of the Liquor Laws has resulted in a decrease in the consumption of traditionally brewed, iron-rich, maize-sorghum beer. The resulting increase in spirit consumption has increased the prevalence of portal fibrosis and cirrhosis. Iron overload was significantly greater in subjects dying from carcinoma of the oesophagus and idiopathic heart failure suggesting excessive exposure of these subjects to traditionally-brewed iron-rich beverages. Serum ferritin concentration, an established measure of iron stores, was used to illustrate an age-related rise in iron stores in a sample of rural black male South trations greater than 200 ^g/l and comparison with the urban autopsy study indicated that iron overload is currently more severe in rural than in urban black males. Geographical differences in serum ferritin concentration showed that iron overload was less common in the northern regions of Southern Africa. Measurements of iron stores, iron deficient erythropoiesis and haemoglobin concentration were necessary to give a comprehensive evaluation of the iron status of a sample of women taken from the South African Indian population. Nearly half the women had evidence of depleted iron stores while the prevalence of iron deficiency anaemia was 14 per cent. Improvement in iron status was related to age and reduced duration of menstruation. A profile of iron status based on the cumulative distribution of calculated iron stores showed that the sample had median iron stores of 150 mg with lower and upper 10 percentiles of -355 mg and 655 mg. Serum ferritin, iron, haemoglobin and placental non-haem iron concentrations were used to study the relationship between maternal and infant iron status at birth. Correlations, similar to those seen in adults, showed that cord serum ferritin concentrations reflect neonatal iron stores. However, its indirect correlation with cord haemoglobin concentration (r = -0.35) suggests that the amount of iron in foetal stores is influenced by that required for haemoglobin and that low serum ferritin concentrations' * do not necessarily indicate reduced iron transfer. Placental non-haem iron was related to maternal serum ferritin concentration (r = 0.^1) but not to measurements of foetal iron status suggesting that stored placental iron is not available to the foetus. Finally the possibility of preventing iron deficiency in the Indian population through the fortification of food with Fe(lll) EDTA was studied. In comparative studies with ferrous sulphate, iron absorption from Fe(lll) EDTA was shown to be significantly less influenced by inhibitors in maize porridge and by bran. Ascorbic acid did enhance absorption but, paradoxically, increased the inhibitory effect of maize porridge. Although curry powder (masala), which is used in large quantities by the Indian population, enhanced iron absorption from both ferrous sulphate and Fe(lll) EDTA, absorption from Fe(lll) EDTA was significantly higher. Evidence that the mechanism whereby Fe(lII) EDTA forms a common pool with intrinsic iron differs from that occurring with simple iron salts, was provided by both the marginally higher absorption from Fe(lll) EDTA than from intrinsic food iron and by studying the exchange of iron between ^Fe(lIl) EDTA and ^FeSO^. This was shown to occur in vitro and the appearance of small amounts of radio-labelled Fe(lll) EDTA in the urine served to demonstrate that the exchange also took place during absorption. p It is concluded that Fe(lll) EDTA may be a useful compound for food fortification of cereals because the iron is well absorbed and utilized for haemoglobin synthesis. The substances in cereals which inhibit absorption of simple iron salts do not appear to inhibit absorption of iron from Fe(lll) EDTA. In addition, the combination of Fe(lll) EDTA and masala as a fortification vehicle is seen to be particularly suitable for a fortification programme in South Africa where such a wide range of iron status is f ound.
Thesis Submitted to the Faculty of Medicine, University of the Witwatersrand, Johannesburg, for the Degree of Doctor of Philosophy Johannesburg, 1981
Keywords: Iron deficiency; Infants; Iron